Evaluation of the extent of reliance to be placed on auditors by the users: Case study of Afrasia Kingdom Zimbabwe Limited. - Zondo, Sherryline (Midlands State University, 2017)
Many world firms like Enron have collapsed while others like Afrasia Kingdom Zimbabwe Limited have gone on the verge of collapsing after auditors have audited without picking any irregularities, for this reason questions are raised on the reliance that can be placed on external auditors. The main objective of this research is to evaluate the extent on which users of the financial statements can rely upon the audit opinion when making economic decisions. Data collection instruments of interviews and questionnaires were used in the research. Secondary sources of data used in the research include published textbooks, journals and the internet. Literature reviewed revealed that auditors can only provide reasonable assurance and not absolute assurance because of the inherent limitations of an audit. Data collected was presented in tables, graphs and pie charts for analysis. Information obtained indicated that users of the financial statements can rely on the audit opinion to a greater extent in making economic decisions since the auditor’s objective is to provide reasonable assurance to both the client and third parties. The research also highlighted that upon negligence, the auditor is fully liable for the opinion they express on the financial statements.